Structural performance and moment redistribution of basalt FRC continuous beams reinforced with basalt FRP bars. (1st August 2021) - Abushanab, Abdelrahman; Alnahhal, Wael; Farraj, Murad
Highlights: The addition of the BMF to concrete mixes improved their flexural tensile strength and ductility. The ductility of BFRP-BFRC beams was improved by increasing the Vf of BMF. The moment redistribution of BFRP-BFRC beams was investigated experimentally. Increasing Sagging-to-hogging reinforcement improved moment redistribution of the beams. A proposed equation incorporating ACI 440.1R-15 guide and a model suggested by Rjoub is proposed. Abstract: This study investigated the structural performance and moment redistribution of basalt fiber reinforced concrete (BFRC) continuous beams reinforced with basalt fiber reinforced polymers (BFRP) bars. A total of 10 reinforced concrete (RC) continuous beams over two equal spans of 1800 mm were tested under five-point loading until failure. The test variables were the type of main bars, sagging-to-hogging reinforcement ratio, volume fractions ( Vf ) of basalt macro fibers (BMF), and stirrups spacing. Seven beams were longitudinally reinforced with BFRP bars, while the remaining three beams were reinforced with conventional steel bars and served as a control. Test results showed that BFRC-RC beams had higher crack widths, mid-span deflections, and strains than steel-RC beams. Furthermore, the ductility index, load-carrying capacities and moment redistribution of the tested beams considerably improved by increasing the Vf of BMF and sagging-to-hogging reinforcement ratio, and decreasing stirrups spacing. However, increasing the reinforcement ratio and Vf of BMF was more effective in improving the moment redistribution than reducing the stirrups spacing. Analytically, the experimental sagging and hogging moments were compared to the available existing models and codes equations. A modified equation incorporating ACI 440.1R-15 provisions and a model suggested by Rjoub provided the most accurate predictions of the tested beams' moment capacities.